1997
DOI: 10.1038/sj.cdd.4400273
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that DNA fragmentation in apoptosis is initiated and propagated by single-strand breaks

Abstract: Apoptosis is characterised by the degradation of DNA into a specific pattern of high and low molecular weight fragments seen on agarose gels as a distribution of sizes between 50 ± 300 kb and sometimes, but not always, a ladder of smaller oligonucleosomal fragments. Using a 2D pulsed fieldconventional agarose gel electrophoresis technique, where the second dimension is run under either normal or denaturing conditions, we show that single-strand breaks are introduced into DNA at the initial stages of fragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…34 There have been a number of reports in the literature suggesting that initiation of apoptotic DNA cleavage occurs at matrix attachment regions. 6,7,[35][36][37] The first supporting evidence came from studies that establish that high molecular weight DNA fragments of 50 and 300 kb, produced in early stages of apoptosis, represent structural domains of chromatin, loops and rosettes, respectively. 1,7 It was then suggested that topoisomerase II, located at matrix attachment sites, is responsible for this cleavage since inhibition of its activity generated the same pattern of DNA fragments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 There have been a number of reports in the literature suggesting that initiation of apoptotic DNA cleavage occurs at matrix attachment regions. 6,7,[35][36][37] The first supporting evidence came from studies that establish that high molecular weight DNA fragments of 50 and 300 kb, produced in early stages of apoptosis, represent structural domains of chromatin, loops and rosettes, respectively. 1,7 It was then suggested that topoisomerase II, located at matrix attachment sites, is responsible for this cleavage since inhibition of its activity generated the same pattern of DNA fragments.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[35][36][37] The first supporting evidence came from studies that establish that high molecular weight DNA fragments of 50 and 300 kb, produced in early stages of apoptosis, represent structural domains of chromatin, loops and rosettes, respectively. 1,7 It was then suggested that topoisomerase II, located at matrix attachment sites, is responsible for this cleavage since inhibition of its activity generated the same pattern of DNA fragments. 6,38 However, others have shown that the activation of endogenous and several exogenous nucleases also results in DNA digestion in the proximity of MARs and produces similar sets of high molecular weight 50 and 300 kb fragments as those generated by topoisomerase II inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in the generation of single-strand breaks (ssb) and, subsequently, double-strand (ds) DNA fragmentation. [15][16][17] Recent reports imply that DNaseY is activated by an increase of intracellular Ca 2 þ , which results in early DNA breaks and activation of PARP-1. Poly-ADP-ribosylation of DNaseY by PARP-1 inhibits its endonuclease activity.…”
Section: Introductionmentioning
confidence: 99%